2019
DOI: 10.1523/jneurosci.1815-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells and Their Derived Cytokine, Interleukin-35, Reduce Pain in Experimental Autoimmune Encephalomyelitis

Abstract: Sensory problems such as neuropathic pain are common and debilitating symptoms in multiple sclerosis (MS), an autoimmune inflammatory disorder of the CNS. Regulatory T (Treg) cells are critical for maintaining immune homeostasis, but their role in MS-associated pain remains unknown. Here, we demonstrate that Treg cell ablation is sufficient to trigger experimental autoimmune encephalomyelitis (EAE) and facial allodynia in immunized female mice. In EAE-induced female mice, adoptive transfer of Treg cells and sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 77 publications
4
50
0
Order By: Relevance
“…Therefore, it is possible that potential neuroprotective activities of TNFR2 in the PNS contribute to its analgesic effects. Further, a recent publication has shown that Tregs reduce pain in EAE via alleviation of neuroinflammation (Duffy et al, 2019). This is in line with our observation that TNFR2 agonism expands Tregs and may indicate that Treg-mediated effects contribute to the analgesic effect of EHD2-sc-mTNF R2 .…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is possible that potential neuroprotective activities of TNFR2 in the PNS contribute to its analgesic effects. Further, a recent publication has shown that Tregs reduce pain in EAE via alleviation of neuroinflammation (Duffy et al, 2019). This is in line with our observation that TNFR2 agonism expands Tregs and may indicate that Treg-mediated effects contribute to the analgesic effect of EHD2-sc-mTNF R2 .…”
Section: Discussionsupporting
confidence: 91%
“…As an example, intrathecal administration of recombinant IL-27 induced antinociception dependent on IL-10 during the maintenance phase of peripheral neuropathy (194). Also, intrathecal delivery of IL-35 in an experimental murine model of autoimmune encephalomyelitis (EAE) reduced pain behaviors (i.e., facial allodynia and grimacing), which was noted to occur through an upregulation of an inflammatory cytokine, IL-10 (195). IL-35 has been very recently highlighted as a candidate target for diabetic neuropathic pain (DNP) treatment (78).…”
Section: Spinal Cordmentioning
confidence: 99%
“…Nav1.8 is a voltage-gated ion channel that mediates action potential firing in nociceptive neurons, and humans with mutations in this ion channel show changes in pain sensitivity. Recent work has shown that Tregs can be potent regulators of pain in mouse models of sciatic nerve injury and experimental autoimmune neuritis (32,33), as well as in experimental autoimmune encephalitis (34). Tregs could modulate pain through several molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%